1977
DOI: 10.1111/j.1399-6576.1977.tb01248.x
|View full text |Cite
|
Sign up to set email alerts
|

Antagonism of Fentanyl with Naloxone during N2O+O2+ Halothane Anaesthesia

Abstract: To investigate the antagonistic effect of naloxone on fentanyl-induced respiratory depression, 55 patients (randomly divided into various study and control groups were studied during nitrous-oxide-oxygen-halothane anaesthesia. Respiratory depression after 0.1 mg of fentanyl was totally reversed by 10 microgram/kg of naloxone, measured as 100% restoration of spontaneous respiration, normal minute volume and end-tidal CO2, while 15 microgram/kg of naloxone was needed to antagonize 0.2 mg of fentanyl. The respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1980
1980
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The respiratory depression following surgery in the patients reported by Adams and Pybus (1978) may be associated with such lack of stimulation, although the event was delayed much longer than the time at which second peaks of fentanyl were observed in the plasma in the present investigation. It is possible that the effects may have been compounded by the usual opiate premedication which was given; however, other data suggest that pethidine has no residual effects (Tigerstedt, 1977). Vejlsted, Hansen and Jacobsen (1977) found that pethidine used as premedication for patients undergoing neuroleptanaesthesia with fentanyl 420 (jtg in divided doses was associated with respiratory depression lasting up to 6 h. It is also possible that fentanyl concentrations in the central nervous system are relatively great at this time.…”
Section: Discussionmentioning
confidence: 99%
“…The respiratory depression following surgery in the patients reported by Adams and Pybus (1978) may be associated with such lack of stimulation, although the event was delayed much longer than the time at which second peaks of fentanyl were observed in the plasma in the present investigation. It is possible that the effects may have been compounded by the usual opiate premedication which was given; however, other data suggest that pethidine has no residual effects (Tigerstedt, 1977). Vejlsted, Hansen and Jacobsen (1977) found that pethidine used as premedication for patients undergoing neuroleptanaesthesia with fentanyl 420 (jtg in divided doses was associated with respiratory depression lasting up to 6 h. It is also possible that fentanyl concentrations in the central nervous system are relatively great at this time.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in patients administered fentanyl anesthesia during surgery have reported that naloxone reversed respiratory depression (Takahashi et al 2004 ; Tigerstedt 1977 ). While these data are intriguing, it is difficult to generalize these results to illicit fentanyl overdose scenarios, which can vary widely with respect to the dose administered and specific fentanyl analog.…”
Section: Naloxonementioning
confidence: 99%